Comment règle-t-on le problème du vol à l'étalage dans les espaces commerciaux français ? - Ocqueteau, Frédéric; Pottier, Marie-Lys (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
Based on the quantitative data derived from the files of various large shopping centers in France, a set of criminal events (i.e. shop-lefting) are analysed. The article meets two concerns : (1) assessing the autonomy of private police via a calculation of the proportion of non-referals of cases to the police and to court and (2) understanding the signification given by private police agents to practices of externalisation of disputes. The key determinant relativising the concept of private policing is the confidence negotiated by the directors of large distribution organizations with public police. In fact, private regulation is not necessarily contradictory with legality, if public actors define their rules on private spaces receiving the public, in matter of policing, after having taken the exact measure of the incidents which affect them.